Double heterotopic pancreas and Meckel’s diverticulum in a child: do they have a common origin? - Baysoy, Gökhan; Balamtekin, Necati; Uslu, Nuray; Karavelioğlu, Afra; Talim, Beril; Ozen, Hasan (The Turkish Journal of Pediatrics, 2010)
Heterotopic pancreatic tissue consists of normally differentiated pancreatic tissue without a real anatomic and vascular connection to the pancreas, whereas Meckel’s diverticulum is one of the most important cause of lower gastrointestinal bleeding in children. Although heterotopic pancreatic tissue is related to various gastrointestinal diseases/malformations in both humans and animals, it is rarely associated with Meckel’s diverticulum. Herein, we report a five-year old boy who presented with melena and hematochezia, which were discovered to be the result of Meckel’s diverticulum. He also had multiple heterotopic pancreatic tissues in various parts of the gastrointestinal tract. The reason for this association is not known, but might involve some abnormalities of signaling molecules expressed in the development of the gastrointestinal tract and associated organs. In clinical practice, it is important to remember that Meckel’s diverticulum and heterotopic pancreatic tissue might occur together or accompany various other gastrointestinal anomalies.